Empowering citizens in conservation of family medicinal plants through processing rosella flowers into tea - Surya Agung Wibowo Mugiyo; Agustina Puspa Mentari; Assaniyah Alfani Al Mubarokah; Afra Nabila Azzahra; Annisa Itsna Nur'aini; Desky Arma Sagita; Fitri Jumiyati; Melita Khusnul Amalia; Mumayizah Mumayizah; Teguh Marwantoro; Tita Roliatun Hasanah; Yulia Permata Sari; Zarra Faizah Zain; Moh Salimi (Universitas Pendidikan Indonesia, 2023)
The quality of health in Indonesia is included in the low category compared to other countries. Based on the results of the GHSI (Global Health Security Index) report, the average global health score is 38.9 points out of a score of 100 points. Meanwhile, Indonesia's global health security index ranks 13th compared to other G20 countries. One of the factors causing a country's low quality of health is caused by the level of a country's economy. This program aims to empower people in the fields of health, economy, and human resources by conserving family medicinal plants from roselle flowers that are processed into tea. The method used in this program is participatory, where environmental scanning is integral to empowering communities through building self-reliance with the power of resources and products. Program results are achieved from the fulfillment of success indicators prepared based on the objectives of the implementation of the program. There are nine main points in the indicators of success that can be achieved. In conclusion, the community empowerment program in Jatimalang Village, Klirong District, Kebumen Regency, has been built from the fulfillment of village-based SDGs and the awareness of the superiority of natural potential owned. Abstrak Kualitas kesehatan di Indonesia termasuk dalam kategori rendah dibandingkan negara lain. Berdasarkan hasil laporan GHSI (Global Health Security Index)skor rata-rata kesehatan global adalah 38,9 poin dari skor 100 poin. Sedangkan indeks ketahanan kesehatan global Indonesia menempati peringkat ke-13 dibandingkan dengan negara G20 lainnya. Salah satu faktor penyebab rendahnya kualitas kesehatan suatu negara disebabkan oleh tingkat ekonomi suatu negara. Tujuan dari program ini adalah memberdayakan warga di bidang kesehatan, ekonomi, dan sumber daya manusia melalui konservasi tanaman obat keluarga dari bunga rosella yang diolah menjadi teh. Metode yang digunakan dalam program ini adalah partisipatif dimana environmental scanning yang merupakan bagian integral dari proses memberdayakan warga melalui membangun kemandirian dengan kekuatan sumber daya dan produk. Hasil program dicapai dari pemenuhan indikator keberhasilan yang disusun berdasarkan tujuan dari dilaksanakannya program tersebut. Terdapat sembilan poin utama dalam indikator keberhasilan yang dapat dicapai. Kesimpulan, program pemberdayaan warga di Desa Jatimalang, Kecamatan Klirong, Kabupaten Kebumen telah dibangun dari pemenuhan SDGs berbasis desa serta dari kesadaran keunggulan potensi alam yang dimiliki. Kata Kunci: Bunga rosella; kesehatan; pemberdayaan warga; tanaman obat keluarga.